Тhe use of textbooks in the learning processfuture doctors and pharmaciststhe disciplines of natural-scientific preparation - Dobrovolska, А. (Problems of Engineer-Pedagogical Education, 2018)
The article is devoted to studying the question of using the author’s manuals in the process of the formation ofinformation technology competence (the IT competence)of future doctors and pharmacists who study the disciplines of naturally scientific preparation. Attention has been focused on the principles which were used during preparation of these manuals, and also the features of their personal orientation have been marked in the process of formation of the IT competence of future specialists. The structural units constituting the developed and implemented manuals for teaching the disciplines of naturally scientific preparation have been characterized. Attention has been focused on that each of these structural units consists of stable, given variable and current variable parts. It has been established that the created manuals can be examined as the complex information-activity model of educational process, which is implemented within the limits of the methodical system of the formation of the IT competenceof future doctors and pharmacists during teaching the disciplines of naturally scientific preparation. The functions of the developed manuals, which are implemented during the formation of the IT competence of future specialists in the process of teaching the disciplines of naturally scientific preparation, have been characterized. It has been found that the use of the noted manuals in the process of teaching the disciplines of naturally scientific preparationprovides the effective formation of the IT competenceof future doctors and pharmacists, which is adequate to the modern requirements on their professional activity in the informative society.